Health problems of stroke patients are forced to reuse with the help of the hospital - Pawłowska, Klaudia (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction Stroke is one of the most important health problems and social, because it is the third leading cause of death in the world – after heart disease and cancer, and in Poland the fourth reason – after accidents. Annually, a million people fall for a stroke. Strokes occur mainly in older people, but they can also occur in young people. Aim The aim of the study was to assess the health problems of stroke patients re-using hospital care. Material and methods The tests were carried out in the Independent Public Health Care Center in Mława, in the Hospital Emergency Department. The study included 60 SOR patients who had had a stroke. The diagnostic survey method was used by conducting a questionnaire. The questionnaire comprised 19 questions addressed directly to the examined person. Results In the group observed most often plagued by ill physical disabilities (36.7 per cent), problems with speech and communication, impede the function (26,6%) patients, while memory issues (18,3%). Rarely have problems with swallowing (11,7%), and depression and depressed mood (6,7%). Conclusions 1 . The respondents are characterized by insufficient knowledge about the lifestyle after a stroke in terms of nutrition, physical activity and abuse of stimulants. 2 . Patients after stroke are partly dependent on the family in helping to perform the basic activities of everyday life. 3 . Early, comprehensive rehabilitation is an indispensable element of treatment for a patient after a stroke.